2017
DOI: 10.1111/phen.12213
|View full text |Cite
|
Sign up to set email alerts
|

Activity of salivary glands in secreting honey‐elaborating enzymes in two subspecies of honeybee (Apis melliferaL)

Abstract: The activity of invertase, glucose oxidase and amylase in the cephalic (post‐cerebral) and thoracic salivary glands is determined in Egyptian and Carniolan honeybees (Apis mellifera L). For this purpose, three ages of worker bees are selected for enzyme assays. The results show that the three target enzymes are detected in the two glands during the three worker ages, except invertase, which cannot be detected in the cephalic gland of newly emerged bees of both subspecies. In both glands, the secretion of inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…The different situation observed for α-glucosidase and β-galactosidase in the presented study indicates different properties of these enzymes, which are manifested by the lack of sensitivity to plant-derived inhibitors. This may be a consequence of their origin from bee throat glands [37]. However, it is only speculation because the knowledge about the source and function of honey enzymes is still being explored.…”
Section: Experiments 2: Addition Of Mulberry Leaves and Fruits During mentioning
confidence: 99%
“…The different situation observed for α-glucosidase and β-galactosidase in the presented study indicates different properties of these enzymes, which are manifested by the lack of sensitivity to plant-derived inhibitors. This may be a consequence of their origin from bee throat glands [37]. However, it is only speculation because the knowledge about the source and function of honey enzymes is still being explored.…”
Section: Experiments 2: Addition Of Mulberry Leaves and Fruits During mentioning
confidence: 99%
“…Honey is a product generated by adult worker bees from flower nectar and different enzymes obtained from secretions of salivary glands, mainly the hypopharyngeal glands. 8,9 In the past, the antibacterial effect of these substances has been mostly attributed to compounds such as methylglyoxal and peroxide, as well as factors such as pH and osmolarity. 10,11 Recently, our group has demonstrated for the first time the presence of exosome-like extracellular vesicles (EVs) in A. mellifera products such as royal jelly, bee pollen and honey.…”
Section: Introductionmentioning
confidence: 99%
“…Invertase is one of the enzymes released from the cephalic and thoracic glands of honey bees and has the highest activity in the maturation of honey (Al-Sherif et al, 2017). When the invertase values obtained within the scope of this study are compared with the ratio of IU≥73.45 recommended by the International Honey Commission (IHC) in terms of proof and freshness of honey not being heat-treated; It was observed that all samples labeled raw honey fit very well with this measurement scale with an average of 188.5±0.2 U/kg (Table 1).…”
Section: Resultsmentioning
confidence: 99%